Monumental memory and identity formation in the Butonese community through the Oputa Yi Koo Monument - Afandi, Muhamat Arif; Febriansyah, Febriansyah (Privietlab, 2025)
This study investigates the role of the Monument of Sultan Himayatuddin Muhammad Saidi (Oputa Yi Koo) in shaping collective memory and social identity among the Butonese community in Baubau, Southeast Sulawesi, Indonesia. Utilizing a qualitative descriptive approach grounded in Maurice Halbwachs' collective memory theory, this study explores how spatial representation, symbolic design, and everyday social practices interact to produce and sustain collective memory. Data were collected through direct observations, visual documentation, and in-depth interviews with local cultural leaders, government officials, and residents. The findings reveal that the monument serves as a socio-symbolic artifact that revives marginalized historical narratives and provides a platform for communal reflection. It becomes a site where the past is reconstructed through present-day needs, reinforcing group identity, while remaining open to reinterpretation and contestation. While many perceive the monument as a source of pride and cultural revival, divergent interpretations of official narratives and community-based memory highlight the collective remembrance's dynamic, negotiated nature. This study argues that monuments are not merely passive heritage objects, but active discursive spaces that mediate identity formation, historical consciousness, and symbolic politics. This research contributes to broader discussions on cultural memory, spatial politics, and heritage making, offering practical insights for inclusive public space design rooted in local historical consciousness.